2020
DOI: 10.21203/rs.3.rs-109131/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental health, coping, and social support among people living with HIV in the Americas: A comparative study between Argentina and the USA during the SARS-CoV-2 pandemic

Abstract: Background: The COVID-19 pandemic pose significant risk to mental health and may disproportionately affect people living with HIV (PLWH). This study examined the interaction of social support and resilient coping in predicting depressive symptoms among PLWH.Methods: PLWH residing in Buenos Aires, Argentina and in Miami, Florida (US) were asked to complete an anonymous survey on the impact of COVID-19. Statistical analysis included ordinary least squares regression.Results: A total of 1,554 participants were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Twenty primary research studies and 33 editorials/commentaries were identified. Sixteen studies were conducted within three countries: the USA, Australia and Turkey, one study was conducted across Belgium and Brazil and the final three studies were conducted across multiple nations [19][20][21][22] (see Table 4 for included countries). Sixteen studies were quantitative, with an additional survey involving open-ended questions, two involved semi-structured qualitative interviews and one detailed a case series (see Table 4).…”
Section: Summary Of Social Impact Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty primary research studies and 33 editorials/commentaries were identified. Sixteen studies were conducted within three countries: the USA, Australia and Turkey, one study was conducted across Belgium and Brazil and the final three studies were conducted across multiple nations [19][20][21][22] (see Table 4 for included countries). Sixteen studies were quantitative, with an additional survey involving open-ended questions, two involved semi-structured qualitative interviews and one detailed a case series (see Table 4).…”
Section: Summary Of Social Impact Studiesmentioning
confidence: 99%
“…The research investigated a range of topics including, mental health and stress [20,21,23,24], access to health care [22,25], experiences of stigma [26], factors impacting medication adherence [27] and social precarity [28]. One US study involved a case series of PLHIV who had been diagnosed with COVID-19 [9] and three studies focused on unique subgroups of PLHIV, including African American and Latinx PLHIV [29], PLHIV with substance use disorders [30] and transgender women living with and without HIV [28].…”
Section: Summary Of Social Impact Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV sufferers generally experience pressure or stress both from within (stress and depression) and from without (stigma and discrimination) to their illness. A number of issues related to coping strategies include age, sex, and sexual orientation, dysfunctional coping (negative coping), as well as various coping techniques and domains that are implemented( 18) (19).…”
Section: Discussionmentioning
confidence: 99%